Transformation and endurance of Indigenous hunting: Kadazandusun-Murut bearded pig hunting practices amidst oil palm expansion and urbanization in Sabah, Malaysia - David J. Kurz; Fiffy Hanisdah Saikim; Vanielie Terrence Justine; Jordan Bloem; Matthew Libass; Matthew Scott Luskin; Lauren S. Withey; Benoît Goossens; Justin S. Brashares; Matthew D. Potts (John Wiley & Sons, 2020)
1. Land-use change and political–economic shifts have shaped hunting patterns globally; even as traditional hunting practices endure across many local socio-cultural contexts. The widespread expansion of oil palm cultivation, and associated urbanization, alters land-use patterns, ecological processes, economic relationships, access to land and social practices. 2. In particular, we focus on the socio-ecological dynamics between Kadazandusun Murut (KDM) hunters in Sabah, Malaysian Borneo, and bearded pigs (Sus barbatus; Malay: ‘babi hutan’), the favoured game animal for non-Muslim communities throughout much of Borneo. We conducted 38 semi-structured interviews spanning over 50 hr with bearded pig hunters, asking them about contemporary hunting practices and motivations, changes in hunting practices, changes in pig behaviour, and patterns of animal protein consumption in village and urban contexts. 3. Amidst widespread land-use change, primarily driven by oil palm expansion, respondents reported substantially different characteristics of hunting in oil palm plantations as compared to hunting in forests. Additionally, 17 of 38 hunters— including 71% (10/14) of hunters who started hunting before 1985, compared to 26% (6/23) of hunters who started hunting in 1985 or later—mentioned that bearded pigs are behaving in a more skittish or fearful way as compared to the past. Our respondents also reported reductions in hunting frequency and wild meat consumption in urban contexts as compared to rural contexts. 4. However, despite these substantial changes in hunting and dietary practices, numerous KDM hunting motivations, hunting techniques and socio-cultural traditions have endured over the last several decades. For some, bearded pig meat remains deeply tied to food provision, gifting and sharing customs, and cultural components of celebrations and feasts. 5. Oil palm has cultivated new hunting practices that differ from those in forests, and has potentially contributed to altered bearded pig behaviour due to increased hunting accessibility. Together, oil palm and urbanization are helping reshape the KDM bearded pig socio-ecological system. In light of these reshaped connections, we recommend location-specific management approaches that ensure fair access to the dietary and social benefits of bearded pig hunting while preserving the critical conservation needs of bearded pig populations and habitat. These twin goals are particularly urgent given the confirmed outbreak of African Swine Fever (ASF), and mass deaths of domestic pigs and wild bearded pigs, in Sabah and Kalimantan in 2021.